Bio-based fertilizers typically deliver on either high nutrient release or soil health parameters - Tine Engedal; Bianca Messmer; Jakob Magid; Lars Stoumann Jensen; Veronika Hansen (Geoderma)
The transition to a circular and bio-based economy requires nutrient recycling from agricultural, industrial, and societal by-products and wastes. Beyond their role in nutrient supply for crop production, bio-based fertilizers (BBFs) also have the potential to improve soil health by contributing organic matter. However, as the legal framework evolves and a broader range of BBFs becomes available, a key challenge for implementation and adaptation lies in the great variability of their nutritional value and effects on soil health. Therefore, the aim of this study was to examine the effects of a diverse sample of BBFs on both nutrient release (nitrogen, sulfur and phosphorus) and a range of soil health parameters. In an 11-month incubation study, we evaluated eleven different bio-based fertilizers: four digestates, two composts, insect frass, and by-products from animal, medicinal, and plant production and processing. The results revealed a trade-off between high nutrient release and soil health improvements. High N availability was significantly and negatively correlated to all examined soil health parameters, while most soil health parameters were positively linked to the amount of added carbon (C). To overcome the trade-off between nutrient availability and soil health, customized BBF blends with optimized nutrient and C profiles tailored to specific field needs may offer a practical solution for farmers. Further research, particularly under field conditions, is needed to fully understand the long-term effects of BBFs on soil properties and crop growth.